Analisis Kebijakan Program Mentoring untuk Meningkatkan Kemampuan Guru di SDN Lulut 2 : Dampaknya terhadap Kinerja dan Motivasi dengan CIPP - Lilis Aenun Zariah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to analyze the policy of the mentoring program implemented at SDN Lulut 2 and its impact on teachers' performance and motivation. Using the CIPP evaluation model (Context, Input, Process, Product), this research assesses the effectiveness of the policy through both quantitative and qualitative data collection. Data were gathered through surveys of teachers and interviews with the school principal and education observers. The results show that the mentoring program has a positive influence on improving teachers' performance, especially in teaching and classroom management, and enhances teachers' motivation for continuous professional development. Additionally, the input and process factors of the mentoring program were found to significantly affect the outcomes. This policy is considered effective in supporting the professional development of teachers at SDN Lulut 2.